Immunoassay platform with surface-enhanced resonance Raman scattering for detecting trace levels of SARS-CoV-2 spike protein - Bistaffa, Maria J. [UNESP]; Camacho, Sabrina A. [UNESP]; Pazin, Wallance M. [UNESP]; Constantino, Carlos J.L. [UNESP]; Oliveira, Osvaldo N.; Aoki, Pedro H.B. [UNESP] (Elsevier, 2022)
The early diagnosis of Coronavirus disease (COVID-19) requires either an accurate detection of genetic material or a sensitive detection of viral proteins. In this work, we designed an immunoassay platform for detecting trace levels of SARS-CoV-2 spike (S) protein. It is based on surface-enhanced resonance Raman scattering (SERRS) of methylene blue (MB) adsorbed onto spherical gold nanoparticles (AuNPs) and coated with a 6 nm silica shell. The latter shell in the SERRS nanoprobe prevented aggregation and permitted functionalization with SARS-CoV-2 antibodies. Specificity of the immunoassay was achieved by combining this functionalization with antibody immobilization on the cover slides that served as the platform support. Different concentrations of SARS-CoV-2 antigen could be distinguished and the lack of influence of interferents was confirmed by treating SERRS data with the multidimensional projection technique Sammon's mapping. With SERRS using a laser line at 633 nm, the lowest concentration of spike protein detected was 10 pg/mL, achieving a limit of detection (LOD) of 0.046 ng/mL (0.60 pM). This value is comparable to the lowest concentrations in the plasma of COVID-19 patients at the onset of symptoms, thus indicating that the SERRS immunoassay platform may be employed for early diagnosis.
Keywords: Conjugation in gold nanoparticles; Resonant Raman molecules; SARS-CoV-2 antibodies; SARS-CoV-2 spike protein detection; SERRS immunoassay Platform; Silica shell functionalization